Effects of antiretroviral combination therapies F/TAF, E/C/F/TAF and R/F/TAF on insulin resistance in healthy volunteers: The TAF-IR Study. Issue 7 (October 2018) - Spinner, Christoph D; Schulz, Sebastian; Bauer, Ulrike; Schneider, Jochen; Bobardt, Johanna; Werder, Alexander Von; Schmid, Roland M; Zink, Alexander; Wolf, Eva; Iakoubov, Roman
Background: Increased insulin resistance (IR), associated with specific antiretroviral drugs or drug classes, is an established risk factor for type 2 diabetes in HIV patients, ultimately increasing morbidity and mortality. To date, data on the risk of IR in tenofovir alafenamide (TAF)-based protocols are unavailable. Methods: This prospective randomized, open-label study evaluated the effects of IR on 30 healthy volunteers receiving fixed-dose combinations (FDCs) of emtricit-abine/tenofovir alafenamide (F/TAF), elvitegravir/cobi-cistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) or rilpivirine/emtricitabine/tenofovir alafenamide (R/F/TAF). IR was measured before and after 14-day treatments using the hyperinsulinemic-euglycaemic clamp technique (HEGC). Changes in IR in each group were evaluated using the mean glucose disposal rate, normalized with body weight (MBW [mg glucose/(minxkg)]). Results: A total of 30 subjects underwent randomization: one subject in the F/TAF arm withdrew consent after randomization and one in the R/F/TAF arm had to be excluded because of technical failure during HEGC, resulting in 28 subjects in the per-protocol population (F/TAF, n =9 subjects; E/C/F/TAF, n =10 subjects; R/F/TAF n =9 subjects). No significant differences were detected on the baseline characteristics. IR did not differ among the groups before treatment. None of the studied anti-retroviral combinations resulted in a significant change in IR after 14 days compared with baseline values, as measured by MBW (F/TAF, 11.42 ±3.04 mean [±sd ] versus 11.43 ±3.23, P =0.49; E/C/F/TAF, 10.04 ±2.49 versus 10.95 ±4.26, P =0.30; R/F/TAF, 11.03 ±1.96 versus 13.01 ±4.11, P =0.13). Conclusions: Short-term treatment for F/TAF, E/C/F/TAF or R/F/TAF did not increase IR in healthy male volunteers.